Learning Management System Using Scorm and iSpring Free on Physics Learning - Aep Setiawan; Mahfuddin Zuhri; Yakin Zhang (Universitas Pakuan, 2022)
This study aims to use a learning management system (LMS) as learning media by using SCORM and iSpring free. This research used the ADDIE Model, which consists of 5 stages: Analysis, Design, Develop, Implement, and Evaluate. The ADDIE method facilitates the process of making learning media. The online learning process using LMS helps students to make good use of technology. Using SCORM and iSpring free in LMS helps students easily access material and do quizzes without time and location limits. Learning materials and quizzes using SCORM and iSpring 9 free are successfully created.